Adhesive for high-toughness impregnated bond paper and preparation method thereof

By modifying isocyanate polymers and rosin-modified melamine-formaldehyde resins, combined with solid fillers and emulsifiers, the toughness and bonding properties of impregnated adhesive film paper are improved, and the lack of toughness and high production costs in the prior art are solved. The problem of efficient adhesive preparation is achieved.

CN119243508APending Publication Date: 2025-01-03INST OF WOOD INDUDTRY CHINESE ACAD OF FORESTRY

Patent Information

Application Number
CN202411380447.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing impregnated adhesive film paper is insufficient in toughness, which is prone to cracking due to changes in the moisture content of the substrate. The existing high-tough adhesives are costly and complex in production, making them difficult to promote and apply.

Method used

Modified isocyanate polymers by casein to form foamed honeycomb polyurethane flexible bodies, and the reaction site of melamine-formaldehyde resin is increased through rosin to form a porous flexible polymer containing air, combining solid fillers and emulsifiers to improve glue Toughness and bonding properties of adhesives.

Benefits of technology

The adhesive for high-toughness impregnated film paper has a simple production process, high toughness and excellent bonding performance, which solves the cracking problem and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243508A_ABST
    Figure CN119243508A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of artificial board processing, in particular to an adhesive for high-toughness impregnated bond paper and a preparation method thereof, and the adhesive comprises the following components: 50-70 parts of melamine, 20-30 parts of formaldehyde solution, 9-29 parts of modified foamed honeycomb type polyurethane flexible body, 1-3 parts of polyvinyl alcohol, 1-5 parts of rosin, 1-5 parts of solid filler, 2-8 parts of emulsifier, 0.05-0.1 part of pH regulator and 60-90 parts of water. Through a strategy of combining internal toughening modification (a flexible foaming method) and external toughening modification (flexible polymer blending and filler modification), a melamino-formaldehyde system of the prepared adhesive has very excellent toughness, and the problem that impregnated bond paper is easy to crack due to size change caused by inadaptation to the moisture content of a base material is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial board processing, in particular to an adhesive for high-toughness impregnated film paper and a preparation method thereof. Background Art

[0002] Impregnated film paper is an important wood-based panel facing material, which plays a role in protecting and beautifying wood-based paper and its products. Impregnated film paper is generally made of decorative base paper after printing and impregnation. The impregnated film paper facing wood-based panel products produced by melamine formaldehyde adhesive have excellent physical properties such as hardness, wear resistance, and scratch resistance. However, due to the strong and stable three-dimensional network structure formed between the adhesive molecules and the high cross-linking density, the toughness of impregnated film paper is very poor, and it is often prone to cracking due to the dimensional changes caused by the moisture content of the substrate. As people's requirements for the quality of life continue to increase, the need to develop an adhesive for high-toughness impregnated film paper is imminent.

[0003] Natural adhesives (including minerals, animal glue and plant glue, etc.), modified bio-based adhesives (soy protein glue, vegetable oil, lignin, etc.) and polymer resin tough impregnated adhesives (including modified acrylates, polyurethanes), etc. are used to develop high-toughness adhesives for impregnated film paper. These adhesives are mainly used in the manufacture of artificial boards such as particleboards and fiberboards in the wood industry. For example, Zhejiang Agricultural and Forestry University (CN202310977475) proposed a method of preparing fiber flexible materials through biomass components, inorganic components, bonding components and coupling components to solve the surface cracking problem of impregnated film paper veneer artificial boards, but they are prone to mold, poor weather resistance and low bonding strength. Wanhua Chemical Group Co., Ltd. (CN202310009325) used water-based polyurethane, dispersants, penetrants, thickeners, etc. to prepare adhesives for impregnated film paper. The adhesives are easy to penetrate and have good flexibility, but the production cost is high, the preparation process is cumbersome, and it is difficult to promote and apply in the market. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide a high-toughness impregnated film paper adhesive and a preparation method thereof, wherein casein-modified isocyanate polymers are used to form a foamed honeycomb polyurethane flexible body, while rosin is used to increase the reaction sites of melamine-formaldehyde resin to form a porous flexible polymer containing air, and finally solid fillers are used to absorb stress to improve the toughness of melamine-formaldehyde resin. The impregnated adhesive has the characteristics of simple production process, high toughness and excellent bonding performance.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] An adhesive for high-toughness impregnated film paper, comprising the following components:

[0007] 50-70 parts of melamine, 20-30 parts of formaldehyde solution, 9-29 parts of modified foamed honeycomb polyurethane flexible body, 1-3 parts of polyvinyl alcohol, 1-5 parts of rosin, 1-5 parts of solid filler, 2-8 parts of emulsifier, 0.05-0.1 parts of pH adjuster, and 60-90 parts of water.

[0008] The method for preparing the modified flexible foamed honeycomb polyurethane comprises the following steps:

[0009] Step 1: Add 3-6 parts of diisocyanate, 3-12 parts of diol, 1-4 parts of siloxane polymer, 1-5 parts of casein and 1-2 parts of catalyst into a reactor;

[0010] Step 2: Control the stirring paddle to be 45°-55° with the horizontal plane ° Angle, the height of the paddle from the bottom of the reaction container is 1 / 3-1 / 2 of the liquid level, the stirring speed is 200-300r / min, after 2-3h, the remaining 1-3 parts of the catalyst are added, and stirring is continued for 25-30min to obtain a modified foamed honeycomb polyurethane flexible body.

[0011] Preferably, the formaldehyde solution is a solution with a mass fraction of 35-37%.

[0012] Preferably, the diisocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.

[0013] Preferably, the diol is one or more of ethylene glycol, diethylene glycol, and 1,4-butanediol.

[0014] Preferably, the polyvinyl alcohol is an aqueous solution with an average molecular weight of 16000-20000, a viscosity of 4-6cp, and a mass fraction of 10-13%; the siloxane polymer is polydimethylsiloxane; the rosin is a solution diluted with anhydrous ethanol to a mass fraction of 20-30%; and the catalyst is one or both of N,N-dimethylformamide and p-toluenesulfonic acid.

[0015] Preferably, the polydimethylsiloxane is one or more of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane and vinyl-terminated dimethylpolysiloxane.

[0016] Preferably, the solid filler is a titanium dioxide suspension with a particle size of 50-200nm, a mass fraction of 20-23%; a silicon dioxide suspension with a particle size of 50-100nm, a mass fraction of 10-13%; a zinc dioxide suspension with a particle size of 50-100nm, a mass fraction of 10-13%; an aluminum oxide suspension with a particle size of 50-200nm, a mass fraction of 10-13% or a combination of the above.

[0017] Preferably, the emulsifier is one or a combination of sodium dodecyl sulfate, sodium octyl sulfonate, sodium dodecylbenzene sulfonate.

[0018] Preferably, the pH regulator is a sodium hydroxide solution with a mass fraction of 10-13%.

[0019] A method for preparing an adhesive for high-toughness impregnated film paper comprises the following steps:

[0020] S1. Mix 9-29 parts of modified foamed honeycomb polyurethane flexible body, 60-90 parts of water, 20-30 parts of formaldehyde solution, 2-8 parts of diol, 0.05-0.1 parts of pH regulator and 1-5 parts of solid filler, and adjust the temperature to 80-110°C;

[0021] S2. Add 50-70 parts of melamine and stir at 200-300r / min for 20-30min; keep the stirring paddle at 45°-55° with the horizontal plane during the reaction. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3-1 / 2 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0022] S3. Add 1-3 parts of polyvinyl alcohol, 1-5 parts of rosin and 2-8 parts of emulsifier to the pre-emulsion, stir at a speed of 600-900r / min, stir for 5-10min, and let stand for 30-35min to obtain a high-toughness impregnated film paper adhesive.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. Through the combination of internal toughening modification (flexible foaming method) and external toughening modification (flexible polymer blending and filler modification), the melamine formaldehyde system of the prepared adhesive has very excellent toughness, which effectively solves the problem that the impregnated film paper is prone to cracking due to the dimensional changes caused by the moisture content of the substrate.

[0025] 2. In the long-chain polymer system, the molecular weight of the selected reactive polymer is appropriate and the reaction is easy to control; the emulsifier system is a preferred compound emulsifier, which can effectively ensure the stability of the adhesive product; a specific stirring paddle position and angle are selected to make the stirring more uniform, so that the adhesive can better penetrate into the interior of the paper, solving the problem of inter-paper damage of impregnated film paper after impregnation with ordinary resin adhesives.

[0026] 3. The toughness and physical strength of the adhesive impregnated film paper prepared by introducing casein-modified foamed honeycomb polyurethane flexible body, polyol, rosin, filler and emulsifier into the melamine formaldehyde system are better than those of pure melamine formaldehyde adhesive impregnated film paper, far exceeding the requirements of national standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart for preparing the adhesive for high-toughness impregnated film paper. DETAILED DESCRIPTION

[0028] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] See also Figure 1 , the present invention provides a technical solution:

[0030] Example 1

[0031] A method for preparing an adhesive for high-toughness impregnated film paper:

[0032] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, 1 part of casein, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° with the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0033] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of formaldehyde solution with a mass fraction of 35%, the remaining 2 parts of ethylene glycol, diethylene glycol, 1,4-butanediol mixed solution, 0.05 parts of sodium hydroxide solution with a mass fraction of 10%, 1 part of titanium dioxide suspension with a particle size of 50nm, a mass fraction of 20%; silicon dioxide suspension with a particle size of 50nm, a mass fraction of 10%; zinc dioxide suspension with a particle size of 50nm, a mass fraction of 10%; aluminum oxide suspension with a particle size of 50nm, a mass fraction of 10% and a mixed solid filler are mixed evenly, the temperature is adjusted to 80°C, and then 50 parts of melamine are added, and stirred at 200r / min for 20min; the stirring paddle is always kept at 45°C with the horizontal plane during the reaction process. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0034] S3. Add 1 part of polyvinyl alcohol with an average molecular weight of 16000, a viscosity of 4cp, and a mass fraction of 10%, 1 part of a rosin solution diluted to a mass fraction of 20% with anhydrous ethanol, and 2 parts of a mixture of sodium dodecyl sulfate, sodium octyl sulfonate, and sodium dodecylbenzene sulfonate to the pre-emulsion, stir at a speed of 600r / min, stir for 5 minutes, and let stand for 30 minutes to obtain a high-toughness impregnated film paper adhesive.

[0035] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0036] Example 2

[0037] A method for preparing an adhesive for high-toughness impregnated film paper:

[0038] S1. Add 6 parts of diphenylmethane diisocyanate, 12 parts of ethylene glycol, 4 parts of hydroxyl-terminated polydimethylsiloxane, 5 parts of casein and 2 parts of N,N-dimethylformamide into the reactor, and stir the paddle at 55° to the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 2 of the liquid level, the stirring speed is 300r / min, after 3h, the remaining 3 parts of N,N-dimethylformamide are added, and stirring is continued for 30min to obtain a modified foamed honeycomb polyurethane flexible body;

[0039] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 90 parts of water, 30 parts of a 37% formaldehyde solution, the remaining 8 parts of ethylene glycol, 0.1 parts of a 13% sodium hydroxide solution, and 5 parts of a titanium dioxide suspension with a particle size of 200 nm and a mass fraction of 23% were mixed evenly, the temperature was adjusted to 110°C, and then 70 parts of melamine were added, and stirred at 300 r / min for 30 minutes; during the reaction process, the stirring paddle was always kept at 55°C from the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 2 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0040] S3. Add 3 parts of polyvinyl alcohol with an average molecular weight of 20,000, a viscosity of 6 cp, and a mass fraction of 13%, 5 parts of rosin solution diluted to a mass fraction of 30% with anhydrous ethanol, and 8 parts of sodium dodecyl sulfate to the pre-emulsion, stir at a speed of 900 r / min, stir for 10 minutes, and let stand for 35 minutes to obtain a high-toughness impregnated film paper adhesive.

[0041] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0042] Example 3

[0043] A method for preparing an adhesive for high-toughness impregnated film paper:

[0044] S1. Add 4 parts of diphenylmethane diisocyanate, a mixture of dicyclohexylmethane diisocyanate, 7 parts of ethylene glycol, a mixture of diethylene glycol, 3 parts of hydroxyl-terminated polydimethylsiloxane, a mixture of aminopropyl-terminated polydimethylsiloxane, 3 parts of casein and 1 part of p-toluenesulfonic acid into the reactor, and stir the paddle at 50° to the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 2 of the liquid level, the stirring speed is 250r / min, after 2.5h, the remaining 2 parts of p-toluenesulfonic acid are added, and stirring is continued for 27min to obtain a modified foamed honeycomb polyurethane flexible body;

[0045] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 75 parts of water, 25 parts of a 36% formaldehyde solution by mass, the remaining 5 parts of ethylene glycol, a mixture of diethylene glycol, 0.07 parts of a 12% sodium hydroxide solution by mass, 3 parts of a titanium dioxide suspension with a particle size of 100 nm and a mass fraction of 21%; a solid filler mixed with a silicon dioxide suspension with a particle size of 80 nm and a mass fraction of 12% was mixed evenly, the temperature was adjusted to 90°C, and then 60 parts of melamine were added, and stirred at 250 r / min for 25 minutes; during the reaction process, the stirring paddle was always kept at 50°C from the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 2 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0046] S3. Add 2 parts of polyvinyl alcohol with an average molecular weight of 18,000, a viscosity of 5 cp, and a mass fraction of 12%, 3 parts of a rosin solution diluted to a mass fraction of 25% with anhydrous ethanol, and 5 parts of a mixture of sodium dodecyl sulfate and sodium octyl sulfonate to the pre-emulsion, stir at a speed of 750 r / min, stir for 8 minutes, and let stand for 32 minutes to obtain a high-toughness impregnated film paper adhesive.

[0047] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0048] Comparative Example 1

[0049] A method for preparing an adhesive for high-toughness impregnated film paper:

[0050] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° to the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0051] S2. Evenly mix the modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of 35% formaldehyde solution by mass, the remaining 2 parts of ethylene glycol, diethylene glycol, 1,4-butanediol mixed solution, and 0.05 parts of 10% sodium hydroxide solution by mass, adjust the temperature to 80°C, then add 50 parts of melamine, and stir at 200r / min for 20min; during the reaction process, always keep the stirring paddle at a 45° angle to the horizontal plane, and the height of the paddle from the bottom of the reaction container is 1 / 3 of the liquid level. Cool to room temperature and let stand for 30min to obtain an adhesive.

[0052] The decorative base paper is impregnated and dried with the adhesive to obtain impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0053] Comparative Example 2

[0054] A method for preparing an adhesive for high-toughness impregnated film paper:

[0055] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° to the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0056] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of formaldehyde solution with a mass fraction of 35%, the remaining 2 parts of ethylene glycol, diethylene glycol, 1,4-butanediol mixed solution, 0.05 parts of sodium hydroxide solution with a mass fraction of 10%, 1 part of titanium dioxide suspension with a particle size of 50nm, a mass fraction of 20%; silicon dioxide suspension with a particle size of 50nm, a mass fraction of 10%; zinc dioxide suspension with a particle size of 50nm, a mass fraction of 10%; aluminum oxide suspension with a particle size of 50nm, a mass fraction of 10% and a mixed solid filler are mixed evenly, the temperature is adjusted to 80°C, and then 50 parts of melamine are added, and stirred at 200r / min for 20min; the stirring paddle is always kept at 45°C with the horizontal plane during the reaction process. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0057] S3. Add 1 part of polyvinyl alcohol with an average molecular weight of 16000, a viscosity of 4cp, and a mass fraction of 10%, 1 part of a rosin solution diluted to a mass fraction of 20% with anhydrous ethanol, and 2 parts of a mixture of sodium dodecyl sulfate, sodium octyl sulfonate, and sodium dodecylbenzene sulfonate to the pre-emulsion, stir at a speed of 600r / min, stir for 5 minutes, and let stand for 30 minutes to obtain a high-toughness impregnated film paper adhesive.

[0058] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0059] Comparative Example 3

[0060] A method for preparing an adhesive for high-toughness impregnated film paper:

[0061] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, 1 part of casein, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° with the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0062] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of formaldehyde solution with a mass fraction of 35%, the remaining 2 parts of ethylene glycol, diethylene glycol, 1,4-butanediol mixed solution, 0.05 parts of sodium hydroxide solution with a mass fraction of 10%, 1 part of titanium dioxide suspension with a particle size of 50nm, a mass fraction of 20%; silicon dioxide suspension with a particle size of 50nm, a mass fraction of 10%; zinc dioxide suspension with a particle size of 50nm, a mass fraction of 10%; aluminum oxide suspension with a particle size of 50nm, a mass fraction of 10% and a mixed solid filler are mixed evenly, the temperature is adjusted to 80°C, and then 50 parts of melamine are added, and stirred at 200r / min for 20min; the stirring paddle is always kept at 45°C with the horizontal plane during the reaction process. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0063] S3. Add 1 part of a rosin solution diluted to 20% by mass with anhydrous ethanol and 2 parts of a mixture of sodium dodecyl sulfate, sodium octyl sulfonate and sodium dodecylbenzene sulfonate to the pre-emulsion, stir at a speed of 600 r / min, stir for 5 minutes, and let stand for 30 minutes to obtain an adhesive for high-toughness impregnated film paper.

[0064] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0065] Comparative Example 4

[0066] A method for preparing an adhesive for high-toughness impregnated film paper:

[0067] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, 1 part of casein, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° with the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0068] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of a 35% formaldehyde solution by mass, the remaining 2 parts of a mixed solution of ethylene glycol, diethylene glycol, and 1,4-butanediol, and 0.05 parts of a 10% sodium hydroxide solution by mass were mixed evenly, the temperature was adjusted to 80°C, and then 50 parts of melamine were added, and stirred at 200r / min for 20min; during the reaction process, the stirring paddle was always kept at an angle of 45° to the horizontal plane, and the height of the paddle from the bottom of the reaction container was 1 / 3 of the liquid level, and the mixture was cooled to room temperature to obtain a pre-emulsion;

[0069] S3. Add 1 part of polyvinyl alcohol with an average molecular weight of 16000, a viscosity of 4cp, and a mass fraction of 10%, 1 part of a rosin solution diluted to a mass fraction of 20% with anhydrous ethanol, and 2 parts of a mixture of sodium dodecyl sulfate, sodium octyl sulfonate, and sodium dodecylbenzene sulfonate to the pre-emulsion, stir at a speed of 600r / min, stir for 5 minutes, and let stand for 30 minutes to obtain a high-toughness impregnated film paper adhesive.

[0070] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0071] Comparative Example 5

[0072] A method for preparing an adhesive for high-toughness impregnated film paper:

[0073] S1. Add 3 parts of a mixture of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate, 3 parts of a mixture of ethylene glycol, diethylene glycol, and 1,4-butanediol, 1 part of a mixture of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane, and vinyl-terminated dimethylpolysiloxane, 1 part of casein, and 1 part of a mixture of N,N-dimethylformamide and p-toluenesulfonic acid into the reactor, and place the stirring paddle at 45° with the horizontal plane. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, the stirring speed is 200r / min, after 2h, add the remaining 1 part of N,N-dimethylformamide and p-toluenesulfonic acid mixed solution, and continue stirring for 25min to obtain a modified foamed honeycomb polyurethane flexible body;

[0074] S2. The modified foamed honeycomb polyurethane flexible body obtained in step S1, 60 parts of water, 20 parts of formaldehyde solution with a mass fraction of 35%, the remaining 2 parts of ethylene glycol, diethylene glycol, 1,4-butanediol mixed solution, 0.05 parts of sodium hydroxide solution with a mass fraction of 10%, 1 part of titanium dioxide suspension with a particle size of 50nm, a mass fraction of 20%; silicon dioxide suspension with a particle size of 50nm, a mass fraction of 10%; zinc dioxide suspension with a particle size of 50nm, a mass fraction of 10%; aluminum oxide suspension with a particle size of 50nm, a mass fraction of 10% and a mixed solid filler are mixed evenly, the temperature is adjusted to 80°C, and then 50 parts of melamine are added, and stirred at 200r / min for 20min; the stirring paddle is always kept at 45°C with the horizontal plane during the reaction process. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3 of the liquid level, cooled to room temperature, to obtain a pre-emulsion;

[0075] S3. Add 1 part of polyvinyl alcohol with an average molecular weight of 16000, a viscosity of 4cp, and a mass fraction of 10% and 2 parts of a mixture of sodium dodecyl sulfate, sodium octyl sulfonate, and sodium dodecylbenzene sulfonate to the pre-emulsion, stir at a speed of 600r / min, stir for 5 minutes, and let stand for 30 minutes to obtain a high-toughness impregnated film paper adhesive.

[0076] The high-toughness impregnated film paper adhesive is used to impregnate and dry the decorative base paper to obtain the impregnated film paper, and the impregnated film paper is hot-pressed onto the surface of the artificial board to obtain the impregnated film paper veneer artificial board.

[0077] Performance Testing:

[0078] According to national standards GB / T 28995-2012, GB / T 15102-2017 and GB / T 17657-2013, the adhesive for high-toughness impregnated film paper, impregnated film paper and impregnated film paper facing wood-based panels obtained in Examples 1-3 and Comparative Examples 1-5 were tested for relevant physical properties. The test results are shown in Tables 1 and 2 below:

[0079] Table 1 Physical properties of adhesive for high toughness impregnated film paper

[0080] Appearance Solid content / wt% Viscosity / mPa·s Example 1 White and transparent 56 54 Example 2 White and transparent 54 51 Example 3 White and transparent 57 54 Comparative Example 1 Colorless and transparent 44 44 Comparative Example 2 White and transparent 48 47 Comparative Example 3 White and transparent 47 48 Comparative Example 4 Colorless and transparent 48 46 Comparative Example 5 White and transparent 45 45

[0081] Table 2 Physical properties of impregnated film paper and impregnated film paper facing wood-based panels Compared with Example 1, casein, polyvinyl alcohol, rosin, solid filler and emulsifier are not added in Comparative Example 1, and casein, polyvinyl alcohol, solid filler and rosin are not added in Comparative Examples 2-5 respectively compared with Example 1. It can be seen from the test results that the raw material components not added in Comparative Examples 1-5 can significantly change the physical properties of the prepared adhesive. The solid filler added by the present invention combines with the melamine formaldehyde resin network at multiple points to reduce stress concentration, and bonds with the melamine formaldehyde resin to block the triazine rings from approaching each other to reduce the crosslinking density, thereby enhancing the toughness and mechanical properties of the adhesive. The emulsifier prevents the filler from agglomerating and ensures the stability of the adhesive system. Rosin provides multiple reaction sites, reduces the network stress that occurs during the condensation of the melamine formaldehyde resin, and reduces the crosslinking density.

[0082] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An adhesive for high-toughness impregnated film paper, characterized in that: Includes the following components: 50-70 parts of melamine, 20-30 parts of formaldehyde solution, 9-29 parts of modified foamed honeycomb polyurethane flexible body, 1-3 parts of polyvinyl alcohol, 1-5 parts of rosin, 1-5 parts of solid filler, 2-8 parts of emulsifier, 0.05-0.1 parts of pH adjuster, and 60-90 parts of water. The method for preparing the modified flexible foamed honeycomb polyurethane comprises the following steps: Step 1: Add 3-6 parts of diisocyanate, 3-12 parts of diol, 1-4 parts of siloxane polymer, 1-5 parts of casein and 1-2 parts of catalyst into a reactor; Step 2: Control the stirring paddle to be 45°-55° with the horizontal plane ° Angle, the height of the paddle from the bottom of the reaction container is 1 / 3-1 / 2 of the liquid level, the stirring speed is 200-300r / min, after 2-3h, the remaining 1-3 parts of the catalyst are added, and stirring is continued for 25-30min to obtain a modified foamed honeycomb polyurethane flexible body.

2. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The formaldehyde solution is a solution with a mass fraction of 35-37%.

3. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The diisocyanate is one or more of diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate, and lysine diisocyanate.

4. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The diol is one or more of ethylene glycol, diethylene glycol and 1,4-butanediol.

5. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The polyvinyl alcohol is an aqueous solution with an average molecular weight of 16000-20000, a viscosity of 4-6cp and a mass fraction of 10-13%; the siloxane polymer is polydimethylsiloxane; the rosin is a solution diluted with anhydrous ethanol to a mass fraction of 20-30%; and the catalyst is one or both of N,N-dimethylformamide and p-toluenesulfonic acid.

6. The adhesive for high-toughness impregnated film paper according to claim 5, characterized in that: The polydimethylsiloxane is one or more of hydroxyl-terminated polydimethylsiloxane, aminopropyl-terminated polydimethylsiloxane and vinyl-terminated dimethylpolysiloxane.

7. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The solid filler is one or a combination of titanium dioxide suspension with a particle size of 50-200nm and a mass fraction of 20-23%; silicon dioxide suspension with a particle size of 50-100nm and a mass fraction of 10-13%; zinc dioxide suspension with a particle size of 50-100nm and a mass fraction of 10-13%; aluminum oxide suspension with a particle size of 50-200nm and a mass fraction of 10-13%.

8. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The emulsifier is one or a combination of sodium dodecyl sulfate, sodium octyl sulfonate, sodium dodecylbenzene sulfonate.

9. The adhesive for high-toughness impregnated film paper according to claim 1, characterized in that: The pH regulator is a sodium hydroxide solution with a mass fraction of 10-13%.

10. The method for preparing a high-toughness impregnated adhesive for paper according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1. Mix 9-29 parts of modified foamed honeycomb polyurethane flexible body, 60-90 parts of water, 20-30 parts of formaldehyde solution, 2-8 parts of diol, 0.05-0.1 parts of pH regulator and 1-5 parts of solid filler, and adjust the temperature to 80-110°C; S2. Add 50-70 parts of melamine and stir at 200-300r / min for 20-30min; keep the stirring paddle at 45°-55° with the horizontal plane during the reaction. ° Angle, the height of the blade from the bottom of the reaction container is 1 / 3-1 / 2 of the liquid level, cooled to room temperature, to obtain a pre-emulsion; S3. Add 1-3 parts of polyvinyl alcohol, 1-5 parts of rosin and 2-8 parts of emulsifier to the pre-emulsion, stir at a speed of 600-900 r / min, stir for 5-10 minutes, and let stand for 30-35 minutes to obtain a high-toughness impregnated film paper adhesive.

Citation Information

Patent Citations

  • Adhesive for impregnating bond paper and preparation method thereof

    CN116239983A

  • Composite flexible material, biomass fiber flexible material and preparation method and application thereof

    CN117005194B

  • Preparation method of whey protein adhesive specially used for wood

    CN108913092A

  • High-toughness polyurethane adhesive

    CN110903804A

  • Impregnated adhesive film paper facing aldehyde-free artificial board and preparation method thereof

    CN111496948A

Cited By

  • Preparation method of anti-cracking impregnated bond paper veneer plywood

    CN121105146A

  • A nano-reinforced melamine impregnated paper based on an aqueous high molecular synthetic resin and a method for its production

    CN122751601A